Ipsilateral corticotectal projections from the primary, premotor and supplementary motor cortical areas in adult macaque monkeys: a quantitative anterograde tracing study. (9th October 2017) - Fregosi, Michela; Rouiller, Eric M.
Abstract: The corticotectal projection from cortical motor areas is one of several descending pathways involved in the indirect control of spinal motoneurons. In non‐human primates, previous studies reported that cortical projections to the superior colliculus (SC) originated from the premotor cortex (PM) and the primary motor cortex, whereas no projection originated from the supplementary motor area (SMA). The aim of the present study was to investigate and compare the properties of corticotectal projections originating from these three cortical motor areas in intact adult macaques ( n  = 9). The anterograde tracer biotinylated dextran amine was injected into one of these cortical areas in each animal. Individual axonal boutons, both en passant and terminaux, were charted and counted in the different layers of the ipsilateral SC. The data confirmed the presence of strong corticotectal projections from the PM. A new observation was that strong corticotectal projections were also found to originate from the SMA (its proper division). The corticotectal projection from the primary motor cortex was quantitatively less strong than that from either the premotor or SMAs. The corticotectal projection from each motor area was directed mainly to the deep layer of the SC, although its intermediate layer was also a consistent target of fairly dense terminations. The strong corticotectal projections from non‐primary motor areas are in position to influence the preparation and planning of voluntary movements. Abstract : The premotor cortex (PM), supplementary motor area (SMA‐proper; but not Pre‐SMA) and primary motor cortex (M1) project to the ipsilateral superior colliculus. The major new finding is that SMA‐proper gives rise to a substantial corticotectal projection. This SMA projection is similar in strength to that of PM and considerably stronger than that originating from M1. The intermediate and deep layers of the superior colliculus are the main targets. There are very rare terminals contralaterally.